Compensating Farm Workers through Piece Rates: Implications on Harvest Costs and Worker Earnings - Fritz M. Roka (EDIS)
FE792, a 4-page fact sheet by Fritz M. Roka, explains how a piece rate payment system works and its implications on production costs and farm worker earnings. Includes references. Published by the UF Department of Food and Resource Economics, February 2009.